Development Strategy of MSMEs Convection Based on Islamic Economic Perspective : Case Study of Kembar Seragam Sekolah Convection Business - Mufti, Muhammad Ikhsan; Daulay, Aqwa Naser; Harahap, Rahmat Daim (Journal of Applied Business Administration, 2025)
This study aims to analyze the development strategy of Micro, Small, and Medium Enterprises (MSMEs) in convection based on the perspective of Islamic economics. This perspective emphasizes public welfare as a strategic foundation for creating sustainable growth. This research method uses a qualitative method with a case study approach. Data were obtained through in-depth interviews with MSME actors and related parties, direct observation, and document analysis. Data analysis was carried out using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to evaluate internal and external factors that affect MSMEs in convection. The results of the study indicate that although MSMEs face various challenges, such as limited capital and marketing, there are great opportunities to grow through the use of digital technology and innovative marketing strategies. Based on the SWOT analysis, the recommended strategies include strengthening product competitiveness, improving managerial skills, and expanding the market through digital platforms. By integrating the principles of Islamic economics, this strategy is not only oriented towards economic growth but also towards the welfare of the wider community. Based on the results of the IFAS and EFAS analysis, the position of the convection MSMEs is in Quadrant I (Strengths-Opportunities) in the SWOT matrix. This quadrant shows that the convection MSMEs has internal strengths that can be utilized to take external opportunities. This position provides direction for implementing the SO Strategy (Maxi-Maxi Strategy). The results of the analysis show that convection MSMEs have great potential to develop, especially through digital technology-based strategies and collaboration with local communities.